Linking Jet Emission, X-Ray States, and Hard X-Ray Tails in the Neutron Star X-Ray Binary GX 17+2 - Migliari, S.; Miller-Jones, James; Fender, R.; Homan, J.; Di Salvo, T.; Rothschild, R.; Rupen, M.; Tomsick, J.; Wijnands, R.; van der Klis, M. (Institute of Physics Publishing, Inc., 2007)
We present the results of simultaneous radio (VLA) and X-ray (RXTE) observations of the Z-type neutron star X-ray binary GX 17+2. The aim is to assess the coupling between X-ray and radio properties throughout its three rapidly variable X-ray states and during the time-resolved transitions. These observations allow us, for the first time, to investigate quantitatively the possible relations between the radio emission and the presence of hard X-ray tails and the X-ray state of the source. The observations reveal (1) a coupling between the radio jet emission and the X-ray state of the source, that is, the position in the X-ray hardness-intensity diagram (HID); (2) a coupling between the presence of a hard X-ray tail and the position in the HID, qualitatively similar to that found for the radio emission; (3) an indication of a quantitative positive correlation between the radio flux density and the X-ray flux in the hard tail power-law component; (4) evidence for the formation of a radio jet associated with the flaring branch-to-normal branch X-ray state transition; and (5) that the radio flux density of the newly formed jet stabilizes when the normal-branch oscillation (NBO) in the X-ray power spectrum stabilizes its characteristic frequency, suggesting a possible relation between X-ray variability associated with the NBO and jet formation. We discuss our results in the context of jet models.